Biochemical Basis of Anti-Cancer-Effects of Phloretin—A Natural Dihydrochalcone - Choi, Bu Young (Molecules, 2019)
Apple is a rich source of bioactive phytochemicals that help improve health by preventing and/or curing many disease processes, including cancer. One of the apple polyphenols is phloretin [2′,4′,6′-Trihydroxy-3-(4-hydroxyphenyl)-propiophenone], which has been widely investigated for its antioxidant, anti-inflammatory and anti-cancer activities in a wide array of preclinical studies. The efficacy of phloretin in suppressing xenograft tumor growth in athymic nude mice implanted with a variety of human cancer cells, and the ability of the compound to interfere with cancer cells signaling, have made it a promising candidate for anti-cancer drug development. Mechanistically, phloretin has been reported to arrest the growth of tumor cells by blocking cyclins and cyclin-dependent kinases and induce apoptosis by activating mitochondria-mediated cell death. The blockade of the glycolytic pathway via downregulation of GLUT2 mRNA and proteins, and the inhibition of tumor cells migration, also corroborates the anti-cancer effects of phloretin. This review sheds light on the molecular targets of phloretin as a potential anti-cancer and anti-inflammatory natural agent.